2015
DOI: 10.1177/1066896915572682
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Trophoblastic Infiltration Into the Tubal Wall in Ampullary Pregnancy

Abstract: A total of 81 patients with an ampullary ectopic pregnancy undergoing salpingectomy were enrolled in the study. The ampullary pregnancies were classified according to the depth of trophoblastic infiltration into tubal wall as follows: Stage I, limited to mucosa; Stage II, extension to the tubal muscularis; Stage III, complete tubal wall infiltration up to the serosa. An association was observed between serum β-human chorionic gonadotropin (β-hCG) levels and the depth of trophoblastic infiltration. Significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Applying the ROC curve, a serum β-hCG level ≥3,706 mIU/mL was statistically associated with tubal rupture in our study, with a sensitivity of 75% and a specificity of 54.3%. Erol et al [12] reported that β-hCG levels above 4,396 mIU/mL correlated with tubal rupture. Another study group noted that β-hCG levels above 5,590 mIU/mL have a 13.9-fold increased probability of affecting the tubal serosa [13].…”
Section: Discussionmentioning
confidence: 99%
“…Applying the ROC curve, a serum β-hCG level ≥3,706 mIU/mL was statistically associated with tubal rupture in our study, with a sensitivity of 75% and a specificity of 54.3%. Erol et al [12] reported that β-hCG levels above 4,396 mIU/mL correlated with tubal rupture. Another study group noted that β-hCG levels above 5,590 mIU/mL have a 13.9-fold increased probability of affecting the tubal serosa [13].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The remaining two-thirds of tubal pregnancies develop into abortive or obsolete ectopic pregnancies. Erol et al 7 suggest that the increased tubal luminal pressure generated by gestation and an inflammatory reaction to tubal wall necrosis may dilate and weaken the tubal wall, increasing the risk of tubal rupture. 7 However, the exact mechanism has not been clearly identified.…”
mentioning
confidence: 99%
“…A causa primária da GE é a alteração da anatomia tubária, macro e/ou microscópica (De Cecco et al, 1984;Qiu et al, 2011), associada ou não ao prejuízo da atividade ciliar e muscular (Shaw et al, 2010 al., 1994;Klein et al, 1995;Kiss et al, 1997;Cabar et al, 2006;Erol et al, 2015a) e a ultrassonografia (Cacciatore et al., 1990a;Cacciatore, 1990b;Brown et al, 1991;Pereira et al, 2009;Erol et al, 2015b) Kucera et al, 2000).…”
Section: Introductionunclassified